2016
DOI: 10.1007/s11064-016-1848-6
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate and ATP at the Interface Between Signaling and Metabolism in Astroglia: Examples from Pathology

Abstract: Glutamate is the main excitatory transmitter in the brain, while ATP represents the most important energy currency in any living cell. Yet, these chemicals play an important role in both processes, enabling them with dual-acting functions in metabolic and intercellular signaling pathways. Glutamate can fuel ATP production, while ATP can act as a transmitter in intercellular signaling. We discuss the interface between glutamate and ATP in signaling and metabolism of astrocytes. Not only do glutamate and ATP cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 198 publications
2
38
0
1
Order By: Relevance
“…We also observed increased nodal and internodal lengths with aging, despite previous reports of shorter internodal distances in aging spinal cord (Lasiene et al, 2009) and primate CNS (Peters, 2009). A majority of aging axon profiles exhibited diffuse Nav1.6 immunoreactivity with prominent elongation of Caspr labeling, as described previously (Hinman et al, 2006;Lasiene et al, 2009;.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…We also observed increased nodal and internodal lengths with aging, despite previous reports of shorter internodal distances in aging spinal cord (Lasiene et al, 2009) and primate CNS (Peters, 2009). A majority of aging axon profiles exhibited diffuse Nav1.6 immunoreactivity with prominent elongation of Caspr labeling, as described previously (Hinman et al, 2006;Lasiene et al, 2009;.…”
Section: Discussionsupporting
confidence: 66%
“…Although loss of myelin in humans (Kemper, 1994) and myelin changes characterized by splitting, ballooning, and exuberant formation (Feldman and Peters, 1998;Peters et al, 2000;Sandell and Peters, 2002) in brain and optic nerves with aging have been reported, overproduction of myelin allows sheaths to enlarge and accommodate the subsequent increases in the diameters of enclosed axons. Moreover, during aging, the activity of genes involved in myelin synthesis is upregulated (Blalock et al, 2003), so more myelin is added to an axon and the myelin sheath gets thicker and begins to occupy an increasing proportion of the surrounding volume (Lasiene et al, 2009). These results suggest that oligodendrocytes remain active during aging and continue to add lamella to the myelin sheaths of intact nerve fibers so that the myelin becomes thicker (Peters, 2009;Bowley et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations